99mTc Tamoxifen for Imaging Estrogen Receptor Expression in Metastatic Breast Cancer Patient. (March 2020) - Chhabra, Anupriya; Shukla, Jaya; Kumar, Rajender; Laroiya, Ishita; Vatsa, Rakhee; Bal, Amanjit; Singh, Gurpreet; Mittal, Bhagwant Rai
Abstract : Abstract: Estrogen receptor–expressing breast cancer exhibits better prognosis due to responsiveness to antiestrogen treatment. Therefore, knowledge of the estrogen receptor status of a tumor is an important prognostic and predictive indicator in breast cancer. We present noninvasive imaging of estrogen receptors with 99m Tc tamoxifen that can identify the active tumor and approachable sites for biopsy. It may help in selection of patients for hormone replacement therapy and in assessment of receptor status in recurrent disease and also in response evaluation.